A delicate balance : portfolio analysis and management for intelligence information dissemination programs - Landree, Eric (RAND, 2009)
This publication describes the application of the RAND Corporation's Portfolio Analysis and Management Method (PortMan) to the evaluation of the National Security Agency's (NSA) information dissemination program portfolio, which is managed by the NSA Information Sharing Services (ISS) division. RAND's PortMan method enables the data-driven analysis of project portfolios and provides a means to monitor the progress of potentially high-value projects. It also allows portfolio managers to monitor the impact of any mitigation strategies they undertake, ensuring that the portfolio's highest potential value is achieved. For this project, RAND researchers first employed the Delphi method, a process for eliciting group opinion by a series of questionnaires with selective feedback from earlier responses, to collect expert opinion from the ISS Senior Leadership Group. This allowed for an estimation of value and risk for each project. RAND then used these estimates, together with cost information provided by ISS, to develop project rankings and to estimate the expected value-to-cost ratio for each project. RAND selected portfolios of projects that maximized the total expected value for the available program budget using a linear programming method and compared these results to ISS management's funding priorities.